On a novel integration of a multistage absorption heat pump with a balanced humidification-dehumidification desalination unit. (December 2021) - Elbassoussi, Muhammad H.; Ahmed, M.A.; Zubair, Syed M.
Highlights: A novel absorption system coupled with a desalination unit is investigated. A single-double-effect absorption can produce desalinated water and a cooling effect. Energy input from both natural gas and a waste-heat source in the proposed system. Results reveal that the system daily produces 110–225 L of water at 0.0042–0.0068$/l. The system has a coefficient of performance of 1.06 and a gained-output ratio of 4.15–8.5. For optimum performance, the absorber and feed to be around 45 °C, 30–35 °C, respectively. Abstract: This study investigates a novel cooling-desalination system having a single-double-effect absorption heat pump coupled with a humidification-dehumidification desalination unit. A waste-heat source drives the system in addition to natural gas. Using a waste-heat source lowers the cost of the desalinated water and thus gives the proposed system considerable attention in the water market. The results reveal that the system can produce desalinated water of about 110 l per day for 0.0068 $/l with a gained output ratio of 4.15. When the air extraction technique is applied, the daily water production and the gained output ratio increase to 225 l and 8.5, respectively. The corresponding water cost drops to 0.0042 $/l. Besides, the system has a coefficient of performance and cooling capacity of 1.06 and 0.8 kW, respectively. The performance results show that for optimal performance, the absorber and the feed saline water temperatures should be around 45 °C and 30–35 °C, respectively. Further, compared with other absorption/humidification-dehumidification configurations, a promising performance of the proposed system is observed.